A new genus for Psopheticus megalops Takeda, 1989 (Crustacea: Brachyura: Goneplacidae) - Ng, Peter K. L.; Komai, Tomoyuki (Zootaxa, 2011)
A new genus is established for Psopheticus megalops Takeda, 1989, an unusual and poorly known species of goneplacoid crab known only from Japan. The carapace and male gonopods are very distinctive, and easily distinguish it from all other genera. Although its classification in the Goneplacidae has been questioned, its thoracic sternal and other characters clearly argue for its continued retention in this family.